Disparities in time to treatment initiation for rectal cancer patients: an analysis of demographic and socioeconomic factors - Popp, Reed; Bansal, Shivam; Sharan, Seema; Ahmed, Syeda Hoorulain; Sukniam, Kulkaew Belle; Raikot, Swathi; Popp, Kyle; Jiménez, Paola Berríos; Manaise, Harsheen Kaur; Kowkabany, Gabrielle; Attwood, Kristopher; Gabriel, Emmanuel M. (Frontiers in Oncology, 2024)
Background: This study investigated demographic and socioeconomic factors contributing to disparities in the time to treatment for rectal cancer. Subgroup analysis based on age < 50 and ≥ 50 was performed to identify differences in time to treatment among young adults (age < 50) compared to older adults with rectal cancer.Methods: An analysis was performed using data from the National Cancer Database, spanning from 2004 to 2019. The study encompassed 281,849 patients diagnosed with rectal cancer. We compared time intervals from diagnosis to surgery, radiation, and chemotherapy, considering age, sex, race, and socioeconomic variables. Analyses were performed for the entire cohort and for two subgroups based on age (< 50 and ≥ 50).Results: Overall, Hispanic patients experienced longer times to surgery, radiation, and chemotherapy compared to non-Hispanic patients (surgery: 94.2 vs. 79.1 days, radiation: 65.0 vs. 55.6 days, chemotherapy: 56.4 vs. 47.8 days, all p < 0.001). Patients with private insurance had shorter times to any treatment (32.5 days) compared to those with government insurance or no insurance (30.6 and 32.5 days, respectively, p < 0.001). Black patients experienced longer wait times for both radiation (63.4 days) and chemotherapy (55.2 days) compared to White patients (54.9 days for radiation and 47.3 days for chemotherapy, both p < 0.001). Interestingly, patients treated at academic facilities had longer times to treatment in surgery, radiation, and chemotherapy compared to those treated at comprehensive and community facilities. When analyzed by age, many of the overall differences persisted despite the age stratification, suggesting that these disparities were driven more by demographic and socioeconomic variables rather than by age.Conclusion: Significant differences in the time to treatment for rectal cancer have been identified. Hispanic patients, individuals lacking private insurance, Black patients, and patients receiving care at academic facilities had the longest times to treatment. However, these differences were largely unaffected by the age (< 50 and ≥ 50) subgroup analysis. Further investigation into the causes of these disparities is warranted to develop effective strategies for reducing treatment gaps and enhancing overall care for rectal cancer patients.